The Policy of Principals Regarding the Implementations of Library School in Bandung City - Arya, Dian; Silvana, Hana; Damayanti, Damayanti (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2015)
Primary and secondary level of education are essential elements for character building and success of younger generation in developing the nation. Education and learning at this level will very much determine how in the future and individual is able to play role and be competitive in the nationâs development. One of the important element in the strategy of educational learning in school which is often forgotten by decision makers ofÂ principals and library managers is the library. Library operation inÂ schools and mandrassas with a policy that has high legitimacy, should be implemented immediately. How ever, what happened was the opposite. By reason of limited fund, time and energy, many schools choose not to implement the rule about library.Base on this issue, this research studied the policy of principals regarding the implementations of actÂ No. 43 of 2007, Government Regulation No. 19 of 2005 and Ministry of National Education Regulations No. 25 of 2008. The reseach was conducted in 6 schools and the quuesionnare was distributed to 6 prinsipals and 12 library staff in Bandung city. The results showed that understanding of three regulations was in very good category with the score of 1157 out og 1230 for the principals.The same category also applied to the library staff with the score of 1613 out of 1800. This suggests that the principals had known about the organization of school library. Likewise, school librarian have also understood and were able to carry out their duties in accordance with the existing regulations related to the operation of school library.Â Â